Electrical switching of an antiferromagnet - Wadley, P.; Howells, Bryn; Železný, J.; Andrews, C.; Hills, V.; Campion, R.P.; Novák, V.; Olejnik, K.; Maccherozzi, F.; Dhesi, S.S.; Martin, S.; Wagner, T.; et al. (American Association for the Advancement of Science, 2016)
Antiferromagnets are hard to control by external magnetic fields because of the alternating directions of magnetic moments on individual atoms and the resulting zero net magnetization. However, relativistic quantum mechanics allows for generating current-induced internal fields whose sign alternates with the periodicity of the antiferromagnetic lattice. Using these fields, which couple strongly to the antiferromagnetic order, we demonstrate room-temperature electrical switching between stable configurations in antiferromagnetic CuMnAs thin-film devices by applied current with magnitudes of order 106 ampere per square centimeter. Electrical writing is combined in our solid-state memory with electrical readout and the stored magnetic state is insensitive to and produces no external magnetic field perturbations, which illustrates the unique merits of antiferromagnets for spintronics.